RECLAMATION IN THE VIEW OF THE PROTECTION OF MARINE ENVIRONMENT UNDER THE ENVIRONMENTAL LAW AND THE LAW CONCERNING THE MANAGEMENT OF COASTAL AREAS AND SMALL ISLANDS - Husin, Sukanda (UI Scholars Hub, 2017)
People view reclamation, both could bring positive and negative impacts to the environment and the human. Based on the pro and con statements, it is obvious that the role of laws and regulation is inevitable solving this matter and therefore the role of government is urgently needed to mediate the pro and con views on reclamation. In terms of legislation, the Government has passed several laws and regulations to regulate reclamation. This paper is intended to explore legal scheme to create a sustainable reclamation. The paper is also designed to describe the ways to create an environmentally sound or sustainable reclamation through a licensing scheme.